Efeitos das tecnologias de realidade aumentada e virtual como recursos visuoespaciais na aprendizagem de geometria molecular - Silva, Kleyfton Soares da (2024)
This research investigated the effects of didactic interventions mediated by augmented reality (AR) and virtual reality (VR) technologies on the learning of molecular geometry concepts. Given the complexity associated with learning molecular structure, this investigation identifies conceptual errors, visuospatial issues, and the use of digital technologies as important elements for developing effective didactic strategies. Utilizing a qualitative and quantitative, applied approach and an explanatory sequential mixed methods data collection and analysis strategy, the research was organized into three complementary studies. The first study aimed to identify conceptual errors related to molecular geometry through a diagnostic test applied to 55 undergraduate biotechnology students at the University of São Paulo. The results revealed difficulties in transitioning between two-dimensional and three-dimensional representations, emphasizing the need for didactic strategies with multiple representations. The second study, conducted with the same participants from study I, assessed the effect of AR on learning molecular geometry. Students were divided into two groups: one reviewed the subject with the support of a conceptual map with static molecules (group A) and the other with a customized conceptual map with AR (group B). The comparison of performance in the task of constructing physical molecules showed superior performance for group B, suggesting that emotional and attention factors may have contributed to a good spatial perception of the molecules. The third study, conducted at the University of Surrey, evaluated the effect of VR, complemented with other resources, on the understanding of molecular geometry. This study highlighted the set of tasks in the pedagogical intervention as engaging, facilitating learning regardless of students' prior knowledge level, and effective in leveling knowledge among different groups. The study conclusions emphasize the relevance of diagnostic tests to identify conceptual errors and the importance of integrating immersive technologies and practical activities in chemistry education. The findings reinforce the need for carefully planned, implemented, and evaluated didactic strategies to enhance performance in chemistry educational contexts.